Disease modification of breast cancer–induced bone remodeling by cannabinoid 2 receptor agonists. (18th December 2012) - Lozano‐Ondoua, Alysia N; Hanlon, Katherine E; Symons‐Liguori, Ashley M; Largent‐Milnes, Tally M; Havelin, Josh J; Ferland, Henry L; Chandramouli, Anupama; Owusu‐Ankomah, Mabel; Nikolich‐Zugich, Tijana; Bloom, Aaron P; Jimenez‐Andrade, Juan Miguel; King, Tamara; et al.
Abstract: Most commonly originating from breast malignancies, metastatic bone cancer causes bone destruction and severe pain. Although novel chemotherapeutic agents have increased life expectancy, patients are experiencing higher incidences of fracture, pain, and drug‐induced side effects; furthermore, recent findings suggest that patients are severely undertreated for their cancer pain. Strong analgesics, namely opiates, are first‐line therapy in alleviating cancer‐related pain despite the severe side effects, including enhanced bone destruction with sustained administration. Bone resorption is primarily treated with bisphosphonates, which are associated with highly undesirable side effects, including nephrotoxicity and osteonecrosis of the jaw. In contrast, cannabinoid receptor 2 (CB2 ) receptor‐specific agonists have been shown to reduce bone loss and stimulate bone formation in a model of osteoporosis. CB2 agonists produce analgesia in both inflammatory and neuropathic pain models. Notably, mixed CB1 /CB2 agonists also demonstrate a reduction in ErbB2‐driven breast cancer progression. Here we demonstrate for the first time that CB2 agonists reduce breast cancer–induced bone pain, bone loss, and breast cancer proliferation via cytokine/chemokine suppression. Studies used the spontaneously‐occurring murine mammary cell line (66.1) implanted into the femur intramedullary space; measurements of spontaneous pain, bone loss, and cancer proliferation were made. The systemic administration of a CB2 agonist, JWH015, for 7 days significantly attenuated bone remodeling, assuaged spontaneous pain, and decreased primary tumor burden. CB2 ‐mediated effects in vivo were reversed by concurrent treatment with a CB2 antagonist/inverse agonist but not with a CB1 antagonist/inverse agonist. In vitro, JWH015 reduced cancer cell proliferation and inflammatory mediators that have been shown to promote pain, bone loss, and proliferation. Taken together, these results suggest CB2 agonists as a novel treatment for breast cancer–induced bone pain, in which disease modifications include a reduction in bone loss, suppression of cancer growth, attenuation of severe bone pain, and increased survival without the major side effects of current therapeutic options. © 2013 American Society for Bone and Mineral Research